Understory vegetation cover across a post-fire tree density gradient in far northeastern Siberia, 2016-2017 - Heather D. Alexander; Homero Pena; Alison K. Paulson (Arctic Data Center, 2018)
In Siberian larch forests, tree density has multiple consequences for both above- and belowground carbon (C) pools within trees and soils as stands mature, but tree density could also influence understory vegetation cover and associated C pools. The primary objective of this study was to determine how fire-driven changes in tree density affect understory vegetation as stands mature within Cajander larch dominated forests of far northeastern Siberia. During the summers of 2016-2017, we surveyed understory plant communities within a 1940 wildfire perimeter near Cherskiy, Russia. Since 1940, different forest stands within the burn perimeter have developed with different larch tree density, and we surveyed plant communities and associated stand and environmental conditions across 25 stands within the perimeter (3 plots per stand, 75 plots total).